Penetrating eye injuries in children in Ibadan (1998)
A retrospective study was carried out on 60 children under 12 years of age with penetrating eye injuries. This formed 28.7% of all penetrating eye injuries seen in the University College Hospital, Ibadan. Corneal lacerations extending to the limbus was the main type of injury occuring in 65% of the patients. In all, 63% of the patient were males. Visual outcomes was poor in this age group with only 19.3% (11 patients) retaining good vision of 6/12 or better.